Simulation model to improve QoS performance over fixed WiMAX using OPNET - Lawal, I.A. (Maxwell Science Publications, 2013)
Worldwide Interoperability for Microwave Access (WiMAX) Technology is one of the most interesting solutions for broadband wireless access, that provide multimedia traffic and applications through an appropriate QoS management for fixed and mobile devices. In this regard, we attempt to introduce a new distributed model to improve the performance of QoS over fixed WiMAX with respect to parameters including throughput, delay and application response time, to enhance the services that are provided to the end users by minimizing delay, application response time and increasing throughput. A Model was developed based on the proposed new distributed model (Master-Slave), the first scenario comprised of 3 Base Stations (BS) and thirty Subscriber Station (SS) with one Master BS selected by the designed algorithm (Nearest Neighborhood Algorithms). Simulations run while increasing the number of BSs, SSs and master BSs using point-to-multipoint connection with multicast transmission based on Orthogonal Frequency Division Multiplexing (OFDM). The design has been evaluated using the simulation tool OPNET modeler 16.0. The results obtained from the three Scenarios shows significant increase in the network throughput and drastic decrease in network delay and application response time. Furthermore, with help of the distributed Master BSs, the coverage area of WiMAX has been increased. Thus greatly enhances the performance of Quality of service (QoS). Â© Maxwell Scientific Organization, 2013.